Blood Flow Restriction Enhances Rehabilitation and Return to Sport: The Paradox of Proximal Performance - Corbin Hedt, P.T., D.P.T; Patrick C. McCulloch, M.D; Joshua D. Harris, M.D; Bradley S. Lambert, Ph.D (Elsevier, 2022)
The use of blood flow restriction (BFR) within rehabilitation is rapidly increasing as further research is performed elucidating purported benefits such as improved muscular strength and size, neuromuscular control, decreased pain, and increased bone mineral density. Interestingly, these benefits are not isolated to structures distal to the occlusive stimulus. Proximal gains are of high interest to rehabilitation professionals, especially those working with patients who are limited due to pain or postsurgical precautions. The review to follow will focus on current evidence and ongoing hypotheses regarding physiologic responses to BFR, current clinical applications, proximal responses to BFR training, potential practical applications for rehabilitation and injury prevention, and directions for future research. Interestingly, benefits have been found in musculature proximal to the occlusive stimulus, which may lend promise to a greater variety of patient populations and conditions. Furthermore, an increasing demand for BFR use in the sports world warrants further research for performance research and recovery. Level of Evidence: Level V, expert opinion.